SUKSESI DAKWAH DALAM PENDEKATAN MASYARAKAT MODERAT (studi tentang tafsÃ®r al-AdabÃ® al-IjtimÃ¢â€™i pada transformasi problematika dakwah) - Zamakhsyari Abdul Majid (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
This paper aims to critically analyze the succession of da'wah in a community approach and to review the paradigm of scientific development systematically. This study uses a qualitative-descriptive method by trying to explore various works and writings related to the focus of the study, either directly or indirectly. The works are read carefully and then analyzed and interpreted qualitatively according to predetermined study problems. This research is a library research. This result is the message of succession in facing big challenges due to the variety of challenges and the intensity of changing times, and considering the multi-dimensional needs of society or human interests now tend to be more critical because of information disclosure, multi-disciplinary da'wah is very much needed. Da'wah will run optimally if the dynamic factors of human life can be projected to an objective approach to resolution and consider socio-historical and cultural aspects. So that the potential of da'wah in this context makes the existing reality a consideration in the planning of the methodology and approach of the da'wah being carried out. The development of modern science is given space for the existence of da'wah in changing conventional approaches to multinational ones. To achieve this, it requires thinking that is oriented towards local aspects to become global. Emphasis on da'wah in moderate or modern societies can be done substantially because current conditions show that society is increasingly critical, so what is needed is preaching that is oriented towards global transformation and which can accept the conditions of the times and sustainable technological advances.